2020
DOI: 10.1249/mss.0000000000002302
|View full text |Cite
|
Sign up to set email alerts
|

Sitting-induced Endothelial Dysfunction Is Prevented in Endurance-trained Individuals

Abstract: Purpose Prolonged sitting impairs leg endothelial function, which seems to be mediated by a sustained reduction in blood flow-induced shear stress. However, whether regular endurance training is effective in preventing sitting-induced leg endothelial dysfunction remains largely unknown. Herein, we tested the hypothesis that sitting-induced leg endothelial dysfunction is prevented in high endurance-trained individuals. Methods The endurance-trained group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 29 publications
2
32
0
Order By: Relevance
“…In agreement with this, Walsh et al (2017) have shown that when the leg is bent at 90° at the hip and knee during the lateral lying down position, there is a significant decline in popliteal artery FMD, similarly to what has been observed during sitting. This was further accompanied by reductions in mean, anterograde, and retrograde shear rate within the first hour of arterial bending, which partially reflects what has been observed during prolonged sitting ( Thosar et al, 2014 ; Thosar et al, 2015a ; Thosar et al, 2015b ; Morishima et al, 2020a ; Morishima et al, 2020b ). This highlights that turbulent flow patterns induced by arterial bending might also contribute to declines in endothelial function during prolonged sitting.…”
Section: Mechanisms Underlying Inactivity-induced Impairments In Vasc...supporting
confidence: 64%
See 2 more Smart Citations
“…In agreement with this, Walsh et al (2017) have shown that when the leg is bent at 90° at the hip and knee during the lateral lying down position, there is a significant decline in popliteal artery FMD, similarly to what has been observed during sitting. This was further accompanied by reductions in mean, anterograde, and retrograde shear rate within the first hour of arterial bending, which partially reflects what has been observed during prolonged sitting ( Thosar et al, 2014 ; Thosar et al, 2015a ; Thosar et al, 2015b ; Morishima et al, 2020a ; Morishima et al, 2020b ). This highlights that turbulent flow patterns induced by arterial bending might also contribute to declines in endothelial function during prolonged sitting.…”
Section: Mechanisms Underlying Inactivity-induced Impairments In Vasc...supporting
confidence: 64%
“…To date, only two studies have shown significant decline in brachial FMD in response to uninterrupted sitting (i.e., 2.5, and 4 h) ( Cho et al, 2020 ; Headid et al, 2020 ), with one of those two studies showing concomitantly a marked decline in popliteal FMD ( Headid et al, 2020 ). In agreement with Restaino et al (2015) , many others have shown that shorter sitting trials (1–3 h) have detrimental effects on endothelial function not only in the popliteal artery (2.3–4.1% FMD) ( Morishima et al, 2016 ; Restaino et al, 2016 ; Morishima et al, 2017 ; Vranish et al, 2017 ; Morishima et al, 2020a ; Morishima et al, 2020b ) but also in the upstream superficial femoral artery (2.4–2.7% FMD) in young healthy adults ( Thosar et al, 2014 ; Thosar et al, 2015a ; Thosar et al, 2015b ; Ballard et al, 2017 ). In addition, recent studies have found that the common femoral artery is affected by sitting-induced vascular dysfunction, measured by passive leg movement (PLM)-induced hyperaemia ( Garten et al, 2019a ; Garten et al, 2019b ; Decker et al, 2021 ), an alternative method to assess endothelial function ( Gifford and Richardson 2017 ).…”
Section: Acute Effects Of Physical Inactivity On Vascular Function In...supporting
confidence: 59%
See 1 more Smart Citation
“…The population and design of each study are reported in Supplementary Table 1 (see Table, Supplemental Digital Content, Appendix, http://links.lww.com/MSS/C407). From the 31 studies included in the analyses, vascular function was assessed in a total of 484 participants: healthy, 322 (9,10,17,18,20–26,36–49); overweight or obesity, 121 (7,50–52); metabolic syndrome, 5 (53); and T2D, 36 (42,54). No participants from any of the included studies were described as having impaired fasting glucose or impaired glucose tolerance.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to a great increase in computer-based jobs in modern workplaces, a substantial increase in sedentary behaviour has become evident across modern workspaces [ 1 ] Contemporary evidence claims a strong association between the occupational sedentary behaviour and the early cardiometabolic disease risk [ 2 ]. Empirical evidence claims unfavorable vascular effects associated with prolonged sedentary times [ 3 ].…”
Section: Introductionmentioning
confidence: 99%